Human resource management - Megginson, Leon C. (Dame Publications, Inc., 1995)
The purpose of this text is to show that events of the past few decades have revolutionized human resource management. In essence, a "people revolution" is under way, and it is changing the very nature of organizational life and human resource management. The approach used in the text is to integrate the concepts of teachers and researchers with the existing pragmatic and practical experience of human resource practitioners